Determination of Some Trace Elements in Natural Waters by Atomic Absorption Spectroscopy After Preconcentration by XAD-4/GBHA System - Ghorbani, Azam; Najarian, Setareh; Khosropour, Zinab (Asian Journal of Chemistry, 2011)
This work was investigated the preconcentration of Pb, Cu and Cd ions by atomic absorption spectroscopy (AAS) using solid phase extraction. The procedure is based on the retention of analytes in the form of glyoxal-bis-(2-hydroxyanil) (GBHA) complexes on a mini column of XAD-4 resin and subsequent elution with nitric acid. The influence of various analytical parameters including the pH, resin amount, elution factors (concentration and volume of eluting solution), volume of sample solution and amount of ligand on the extraction efficiency of analytes was investigated. The average relative standard deviations of the determinations were below 7 %. The limits of detection for analytes were found in the range of 0.06-0.50 μg L-1. The method was applied to the analysis of trace elements in some natural waters from Hamedan city of Iran.